The Effects of Guided Inquiry Learning with the Assistance of Concept Maps on Students' Scientific Literacy - I Putu Artayasa; Muhlis Muhlis; I Wayan Merta; Gito Hadiprayitno (Jurnal Penelitian Pendidikan IPA, 2021)
The purpose of this study is to examine the effect of the application of the guided inquiry learning model assisted by concept maps on the scientific literacy of junior high school students in the city of Mataram. The research was conducted through a pretest-posttest design with a non-randomized control group. The sampling technique was purposive sampling. The sample of 90 students was divided into three classes, where the first-class applied guided inquiry learning assisted by concept maps, the second class applied inquiry learning without the help of concept maps, and the third class applied conventional learning. All classes were given a pretest and posttest scientific literacy. Data in the form of pretest and posttest scores were analyzed by Analysis of Variance (ANOVA) and continued with the Least Significance Difference (LSD) test at 5% alpha. The results showed that the mean score of students' scientific literacy in the class that applied the guided inquiry learning model assisted by concept maps was significantly higher than the mean score of the conventional class. The conclusion is that there is an effect of the implementation of the inquiry learning model assisted by the concept map method on students' scientific literacy